1995
DOI: 10.1074/jbc.270.15.8712
|View full text |Cite
|
Sign up to set email alerts
|

Acceptor Specificity of Different Length Constructs of Human Recombinant α1,3/4-Fucosyltransferases

Abstract: The acceptor specificity of recombinant full-length, membrane-bound fucosyltransferases, expressed in COS-7 cells, and soluble, protein-A chimeric forms of alpha 1,3-fucosyltransferase (Fuc-T) III, Fuc-TIV, and Fuc-TV was analyzed toward a broad panel of oligosaccharide, glycolipid, and glycoprotein substrates. Our results on the full-length enzymes confirm and extend previous studies. However, chimeric Fuc-Ts showed increased activity toward glycoproteins, whereas chimeric Fuc-TIII and Fuc-TV had a decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
1

Year Published

1998
1998
2003
2003

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(81 citation statements)
references
References 64 publications
5
75
1
Order By: Relevance
“…This fits with previous observations (Kobayashi et al 1993) and probably reflects different FucT III enzyme activities towards different acceptor substrates (e.g. glycolipids vs glycoproteins) (De Vries et al 1995). Seven of the cases with a Lewis positive expression profile in the gastric mucosa are homozygous for one of the deleterious polymorphisms (202T>C, 508G>A or 1067T>A) ( antigens.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This fits with previous observations (Kobayashi et al 1993) and probably reflects different FucT III enzyme activities towards different acceptor substrates (e.g. glycolipids vs glycoproteins) (De Vries et al 1995). Seven of the cases with a Lewis positive expression profile in the gastric mucosa are homozygous for one of the deleterious polymorphisms (202T>C, 508G>A or 1067T>A) ( antigens.…”
Section: Discussionsupporting
confidence: 78%
“…The other two polymorphisms that we identified (202T>C and 314C>T) are localised in the catalytic domain and are associated with a negative Lewis phenotype in Sweden (De Vries et al 1995;Elmgren et al 1996) and in Denmark (Ørntoft et al 1996). Curiously, De Vries et al (1995) showed that the 314C>T polymorphism has enzymatic activity similar to wild type enzyme when it catalyses the Le antigens synthesis on glycoprotein acceptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Properties of pPROTA-expressed enzymes have been shown to be very similar to those of full-length enzymes (26). Site-directed mutagenesis of FucT V in pPROTA forming the two mutants K255R and K255A was conducted as follows via recombinant PCR (19).…”
Section: Methodsmentioning
confidence: 99%
“…The reaction mixture was incubated for 1 h at room temperature and stopped and quantitated as described previously utilizing Dowex-1 for oligosaccharide acceptors (26) or C 18 columns for 8-methoxycarbonyl glycoside derivatives as acceptors (26).…”
Section: Methodsmentioning
confidence: 99%